(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Trigeminal neuralgia (TN) or tic douloureux is one of the commonest cause of fascial pain after 50 years of age. It is characterized by recurrent, episodic, lancinating pain over the distribution of trigeminal nerve. There is a lack of certainty regarding the aetiology and pathophysiology of TN. Evidence suggests that the likely etiology is vascular compression of the trigeminal nerve leading to focal demyelination and aberrant neural discharge. Secondary causes such as multiple sclerosis or brain tumors can also produce symptomatic TN. The treatment of TN can be very challenging despite the numerous options patients and physicians can choose from. This multitude of treatment options poses the question as to which treatment fits which patient best. For patients refractory to medical therapy, Gasserian ganglion percutaneous techniques, gamma knife surgery and microvascular decompression are the most promising invasive treatment options. Among them three common interventions commonly carried out by interventional pain physician to provide pain relief are balloon compression, Glycerol rhizolysis and RF rhizotomy. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 73-77